COMPARATIVE STUDY OF CRIMINAL LAW AND SHARIA LAW (CASE STUDY: MINOR WORKERS) - Aulia, Gavinella; Mandasari Saragih, Yasmirah; Zarzani, T. Riza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
A child is someone who is still underage, whether male or female. The phenomenon of children as workers often occurs. The reality shows that poor families really need jobs for their children to help the family economy and for their own lives. In this research, the author examines "Judicial Review of Child Labor (Study of Positive Legal Analysis and Islamic Criminal Law)", so the author formulates the problem as follows: 1) What is the positive legal view of child labor? 2) What is the view of Islamic criminal law regarding child labor? This research is library research, which is descriptive in nature with a normative approach, namely by using Al-Qur'an texts and is based on other legal products in the form of books, laws and regulations related to the discussion. Based on the research results, the author concludes that children are not allowed to work unless the work they do is light and does not interfere with the child's physical, social and mental health development and meets the requirements in article 69 paragraph 2 of Law Number 13 of 2003 concerning Employment. If you violate the provisions as stipulated in article 185 of Law Number 13 of 2003 concerning Employment, you will be subject to imprisonment for a minimum of 1 (one) year and a maximum of 4 (four) years and/or a fine of at least Rp. 100,000,000 (one hundred million rupiah). and a maximum of Rp. 400,000,000 (four hundred million rupiah), while the sanctions for employing children in Islamic criminal law fall into the category of jarimahta'zir whose punishment is not specified in the Al-Quran and Hadith but is left to the authorities (Judges).